Random conical tilt reconstruction without particle picking in cryo‐electron microscopy. Issue 4 (24th June 2022) - Lan, Ti-Yen; Boumal, Nicolas; Singer, Amit
Abstract : A method is described to reconstruct the 3D molecular structure without the need for particle picking in the random conical tilt scheme. The results show promise to reduce the size limit for single‐particle reconstruction in cryo‐electron microscopy. Abstract : A method is proposed to reconstruct the 3D molecular structure from micrographs collected at just one sample tilt angle in the random conical tilt scheme in cryo‐electron microscopy. The method uses autocorrelation analysis on the micrographs to estimate features of the molecule which are invariant under certain nuisance parameters such as the positions of molecular projections in the micrographs. This enables the molecular structure to be reconstructed directly from micrographs, completely circumventing the need for particle picking. Reconstructions are demonstrated with simulated data and the effect of the missing‐cone region is investigated. These results show promise to reduce the size limit for single‐particle reconstruction in cryo‐electron microscopy.